MELATIH MOTORIK KASAR MELALUI PERMAINAN LOMPAT TALI PADA ANAK PAUD MANDIRI DESA SUKA NEGERI - Annisa Fortuna; Mulia Marita Lasutri Tama; Mutia Mawardah (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2022)
Children who are at an early age (0-6 years) are children who are at a stage of rapid growth and development, both physically and mentally. This period is also called the golden age. In the golden age, early childhood needs encouragement that can support the development of the child so that the child's growth and development is not hampered. Gross motor skills are closely related to the progress, development, and growth of children at an early age. The purpose of this activity is to train gross motor skills such as movements for PAUD Mandiri children in Suka Negeri Village. The method used by the researcher is the playing method through jumping rope because researchers see many children who are still shy in doing physical activities at PAUD Mandiri Suka Negeri Village. During the routine exercise on Friday morning, the researchers saw that the children looked doubtful and reluctant to make specific movements. The enthusiasm of the children when playing jump rope was high, but there were two children who seemed hesitant, three children lost their balance when they were on a rope that reached 30cm, and six children looked confused and needed more guidance when walking in a zigzag without stepping on the rope